2008
DOI: 10.2174/138161208785061409
|View full text |Cite
|
Sign up to set email alerts
|

Novel Preparative Regimens in Hematopoietic Stem Cell Transplantation

Abstract: Hematopoietic stem cell transplantation is an established treatment modality for malignant and non-malignant diseases. Prior to the infusion of allogeneic or autologous cells, patients usually receive radiation or chemotherapy. This "preparative" or 'conditioning' regimen provides treatment for the underlying disease and is expected to impair the recipient's immune system and allow engraftment. The last decade witnessed a significant reduction in treatment-related mortality, in great part a result of less toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Conditioning regimens, chronic immune suppression, and graft-versus-host disease present significant challenges for cellular transplantation (1, 2). To avoid the need to modulate the immune system, cell encapsulation devices have been considered (3, 4).…”
Section: Introductionmentioning
confidence: 99%
“…Conditioning regimens, chronic immune suppression, and graft-versus-host disease present significant challenges for cellular transplantation (1, 2). To avoid the need to modulate the immune system, cell encapsulation devices have been considered (3, 4).…”
Section: Introductionmentioning
confidence: 99%
“…Such myeloablative conditioning regimens can potentially lead to a high incidence of transplant related complications that may result in patient mortalities. However, in the last two decades, there has been a significant reduction in transplant related mortality (TRM), largely because of the use of less toxic, yet effective, preparative regimens as well as improvements in supportive care [16]. Traditional conditioning regimens have been enhanced by the incorporation of newer drugs that target specific hematopoietic cells (like rituximab) as well as other drugs with less toxicity and higher anti-tumor effects like treosulfan [17], thiotepa [18] and radiolabelled antibodies [19].…”
Section: Improving Hsct Outcomes Novel Preparative Regimens and Suppomentioning
confidence: 99%
“…blood precursor cells (PBPC) and a better support therapy [26]. In the CORAL trial, there were three deaths reported (TRM 1.4%) due to toxicity among 206 chemosensitive relapsed patients with DLBCL after BEAM [27].…”
Section: Review Musso Porretto Scalone Crescimanno Polizzi and Bonannomentioning
confidence: 99%